Synergy Between The Judicial Commission and The Supreme Court in Supervising Judges: Strengthening Accountability Without Harming The Independence of The Judicial Power - Amil Shadiq (International Journal of Science and Environment (IJSE), 2026)
Judicial oversight constitutes a crucial instrument in preserving the integrity, accountability, and public trust in the judiciary. Within the Indonesian constitutional framework, judicial oversight is exercised by two principal institutions: the Judicial Commission as the external supervisory body focusing on the honor, dignity, and conduct of judges, and the Supreme Court as the internal supervisory body emphasizing institutional discipline as well as technical and administrative oversight. In practice, however, the relationship between these institutions has not functioned in a fully synergistic manner. The main problems include overlapping perceptions of authority, weak follow-up on the Judicial Commission’s recommendations, institutional resistance, limited resources, and suboptimal public participation. This study aims to analyze the construction of authority of the Judicial Commission and the Supreme Court in judicial oversight, identify factors inhibiting effective supervision, and formulate an institutional synergy model that remains respectful of judicial independence. This research employs normative legal research using statutory and conceptual approaches. The study finds that the principal issue lies not in the existence of dual supervisory institutions, but in the absence of an operational and procedurally binding coordination design supported by an open institutional culture.